Use of nano-/micro-magnetite for abatement of cadmium and lead contamination. (15th June 2020) - Ajmal, Zeeshan; Usman, Muhammad; Anastopoulos, Ioannis; Qadeer, Abdul; Zhu, Runliang; Wakeel, Abdul; Dong, Renjie
Abstract: Structural variations of a mineral dictate its adsorption capacity which affects the mobility and toxicity of contaminants in natural and engineered systems. Present batch study evaluates the adsorption of lead (Pb) and cadmium (Cd) onto three magnetites having nanometric (M1-30 nm and M2-60 nm) and micrometric particle sizes (M3-1.5 μm). Obtained data revealed that particle size of tested magnetites strongly affected the extent and kinetics of metal adsorption and desorption. Observed order of adsorption efficiency was M1 > M2 > M3 with optimum monolayer adsorption of 408.14, 331.40, 178.47 mg/g (for Pb) and 228.05, 170.86, 83.49 mg/g (for Cd), respectively. Adsorption data were well fitted to the Freundlich (R 2  = 0.99), Langmuir (R 2  = 0.99) and pseudo-first order models (R 2  = 0.98). Electrostatic attraction and surface precipitation interaction via external mass transfer between bulk liquid-solid interfaces were the potential adsorption pathways. Pb showed higher affinity than Cd in multi-metal system. Desorption efficiency was higher in acidic environment (92%) than in distilled water (44%). Moreover, regenerated magnetite samples retained good adsorption capacity for six cycles. As soils are characterized by large variability of iron minerals, these findings have important implications regarding the transport and immobilization of contaminants particularly in the management of contaminated soils. Highlights: Adsorption/desorption characteristics of three magnetites to adsorb Pb and Cd. Nano-magnetite exhibited strong adsorption and regeneration potential. Data better fitted to Freundlich, Langmuir and pseudo-first order models. Higher desorption in acidic environment (92%) than in distilled water (44%). Strong implications in soil immobilization and pollutant fate.